Державні гарантії соціального захисту працівників слідчих підрозділів поліції - Рекун, С. С.; Rekun, S. S. (Науковий вісник публічного та приватного права. - 2021. - Вип. 2, т. 2. - С. 168-172, 2021)
Запропоновано авторське бачення щодо тлумачення поняття «державні гарантії соціального захисту працівників слідчих підрозділів поліції». Розкрито зміст норм чинного законодавства, в якому закріплюються ключові гарантії соціального захисту досліджуваної категорії працівників. Акцентовано увагу на недоліках, які заважають повною мірою реалізувати державні гарантії у відповідній сфері. Наголошено, що незважаючи на досить широкий перелік гарантій соціального захисту працівників слідчих підрозділів, недосконалими є механізми реалізації деяких із них.

The relevance of the article lies in the fact that the work of investigative units of the National Police of Ukraine depends on many factors, among which, of course, the key place belongs to social protection. The importance of social protection of the investigated category of workers is explained by the fact that, through the appropriate system, the legislator has the opportunity to create such conditions under which investigators and their family members will feel confident "in the future", and therefore more effectively perform their official duties. It is worth noting that the social protection of employees of police investigative units requires the creation of a number of tools, conditions and means for its implementation. The set of the latter is usually called guarantees, the peculiarity of which is due to the specifics of the legal status of the studied category of employees, as well as the peculiarities of the legal regulation of their labor activities. In the article, based on the analysis of the scientific views of scientists, the author's vision is proposed regarding the interpretation of the concept of "state guarantees of social protection for employees of police investigative units." The content of the norms of the current legislation, which enshrines the key guarantees of social protection of the studied category of workers, is disclosed. Attention is focused on the shortcomings that prevent the full implementation of state guarantees in the relevant field. It was concluded that despite a rather wide list of guarantees of social protection for employees of investigative units, the mechanisms for implementing some of them are imperfect. Thus, the problems in the specified sphere should include: firstly, a rather extensive system of legislative regulation of social relations in the relevant sphere, which leads to the emergence of legal conflicts; secondly, there is no single regulatory document, the provisions of which are aimed directly at regulating the issue of social protection of police officers in general and employees of investigative units, in particular; thirdly, the absence of effective state programs and mechanisms for the implementation of individual guarantees of social protection, in particular regarding housing and medical care for police officers and their family members.

Предложено авторское видение толкования понятия «государственные гарантии социальной защиты работников следственных подразделений полиции». Раскрыто содержание норм действующего законодательства, где закрепляются ключевые гарантии социальной защиты исследуемой категории работников. Акцентировано внимание на недостатках, мешающих в полной степени реализовать государственные гарантии в соответствующей сфере. Отмечено, что несмотря на достаточно широкий перечень гарантий социальной защиты работников следственных подразделений, несовершенны механизмы реализации некоторых из них.
State guarantees of social protection of employees of police investigative units
Keywords: слідчі підрозділи; investigative units; следственные подразделения; працівники; employees; работники; Національна поліція України; National Police of Ukraine; Национальная полиция Украины; державні гарантії; state guarantees; государственные гарантии; соціальний захист; social protection; социальная защита